Barriers and enablers to physical activity and aerobic fitness deficits among childhood cancer survivors. Issue 7 (9th May 2020) - Mizrahi, David; Wakefield, Claire E.; Simar, David; Ha, Lauren; McBride, James; Field, Penelope; Cohn, Richard J.; Fardell, Joanna E.
Abstract: Background: Physical activity and aerobic fitness are modifiable risk factors for cardiovascular disease (CVD) after childhood cancer. How survivors engage in physical activity remains unclear, potentially increasing CVD risk. We assessed survivors' physical activity levels, barriers and enablers, fitness, and identified predictors of fitness and physical activity stage of change. Methods: Childhood cancer survivors (CCS; 8‐18 years old) ≥1 year post‐treatment were assessed for aerobic fitness (6‐min walk test), used to extrapolate VO2max, and body composition (InBody 570). Survivors self‐reported physical activity to determine stage of change (Patient‐Centered Assessment and Counselling for Exercise). Physical activity and fitness were compared with guidelines and CVD‐risk cut‐points (VO2max < 42 mL/kg/min: males; VO2max < 35 mL/kg/min: females). Multiple regression and mediator‐moderator analysis were used to identify fitness predictors and stage of change. Results: One hundred two survivors (12.8 ± 3.3 years) participated (46% acute lymphoblastic leukaemia). Forty percent of males (VO2max = 43.3 ± 6.3 mL/kg/min) and 28% of females (VO2max = 36.5 ± 5.9 mL/kg/min) were in the CVD‐risk category, while 25% met physical activity guidelines. Most prevalent physical activity barriers were fatigue (52%), preferring television instead of exercise (38%), and lacking time (34%). Predictive factors for reduced fitness included being older, female, higher waist‐to‐height ratio, higher screen time, and moderated by lower physical activity ( r 2 = 0.91, P < .001). Survivors with higher physical activity stage of change were male, lower body fat percentage, lower screen time, and lived with both parents ( r = 0.42, P = .003). Conclusion: Aerobic fitness and physical activity of CCS is low compared with population norms, potentially increasing CVD risk. Addressing physical activity barriers and enablers, including reducing screen time, could promote regular physical activity, reducing CVD risk.